Breast cancer therapies reduce risk of Alzheimer's disease and dementia: A claims‐based retrospective study with clinic to bench implications. (31st December 2021) - Branigan, Gregory L; Torrandell‐Haro, Georgina; Brinton, Roberta Diaz
Abstract: Background: Worldwide, breast cancer is the most common non‐skin cancer in women. Currently, Alzheimer's disease affects 1 in 9 persons in the US over the age of 65, two thirds of whom are women. The high global prevalence and economic impact of Alzheimer's disease presents a significant public health challenge while the identification of therapies to prevent Alzheimer's disease (AD) remains a challenge. The object of this study was to determine whether estrogen modulating therapy (EMT) exposure is associated with risk of Alzheimer's (AD) in women with breast cancer in the Symphony claims data set and identify potential mechanisms by which these drugs may impact risk. Methods: Patients receiving EMT for breast cancer treatment were identified and survival analysis, stratified by age and by individual therapeutics, was used to determine the association between EMT exposure and diagnosis of AD. A propensity score approach was used to minimize measured and unmeasured selection bias. The impact of the impact of EMT on mitochondrial bioenergetics and dynamics were determined using Metabolic flux analysis and live cell imaging using Rat E18 hippocampal neurons. Results: In this cohort study of propensity score matched perimenopausal to postmenopausal aged women with breast cancer, EMT exposure was associated with decrease in diagnosis of neurodegenerative disease, most specifically AD (RR, 0.85; 95% CI, 0.78‐0.92; P < 0.001) and Dementia (RR, 0.88; 95% CI, 0.84‐0.93; P < 0.001). The preventative effect of EMT was shown to increase with age and was associated with a 5‐year shift in disease conversion rate. Mitochondrial bioenergetic data suggest that tamoxifen and the aromatase inhibitors show estrogen‐like response. Conclusion: Among female patients with breast cancer, exposure to estrogen modulating therapies was associated with a decrease in diagnosis of AD and Dementia. If tamoxifen and aromatase inhibitors are acting to increase estrogen‐related actions in brain tissue, the argument for the protective association of estrogen with AD‐related outcomes is strengthened. Funding: This study was supported by grants from the Women's Alzheimer's Movement, National Institute on Aging grants P01AG026572 Perimenopause in Brain Aging and Alzheimer's Disease and T32AG061897 Translational Research in AD and related Dementias (TRADD) to RDB.